Analisis bibliometrik tren penelitian strategi pemasaran perpustakaan tahun 2005 – 2025 - Nurcahyani, Desi; Erwina, Wina; CMS, Samson (FPPTI Jawa Tengah, 2025)
This study aims to analyze the development of research on library marketing strategies from 2004 to 2024 using a bibliometric approach. A quantitative descriptive bibliometric method was employed, with data retrieved from the Scopus database using the keywords